SOLPS-ITER modeling of CFETR advanced divertor with Ar and Ne seeding. (1st September 2022) - Senichenkov, I.Yu.; Ding, R.; Molchanov, P.A.; Kaveeva, E.G.; Rozhansky, V.A.; Voskoboynikov, S.P.; Shtyrkhunov, N.V.; Makarov, S.O.; Si, H.; Liu, X.; Sang, C.; Mao, S.; et al.
Abstract: The Chinese Fusion Engineering Testing Reactor (CFETR) is a project proposed by the Chinese fusion community to bridge the gap between ITER and a commercial fusion power plant with fusion power up to 1 GW. The mitigation of divertor target heat fluxes for such a powerful machine is a challenging problem, which might appear to be more severe than in ITER. In the present paper, the results of the CFETR advanced divertor optimization by SOLPS-ITER modeling with full drifts and currents activated are presented. Three divertor geometries, which differ by the distance from the X -point to the strike point on the outer target, are considered. Argon (Ar) and neon (Ne) are compared as seeded impurities. It is demonstrated that for all three geometries and for both radiators it is possible to achieve acceptable divertor heat loads (below 5 MW m −2 ) without notable fuel dilution ( Z eff < 2.5). Impurity compression in divertors and pedestal radiation are compared for two gases. Similar core plasma and divertor conditions, as well as radiated power fraction, may be achieved with 2–3 times less Ar seeding rate than the Ne one. Estimated radiation from the confined region appears to be small compared to the exhaust power. However, in all modeling cases the T e at the far scrape-off layer part of both targets remains significantly above 5 eV, which might cause tungsten (W) sputtering. Further optimization of target shape will be performed to reduce the electron and ion temperature.